THE POTENCY AND USE OF Tamarindus indica ON VARIOUS THERAPIES - Putri, Candra Rini Hasanah (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2014)
The use of natural materials for medical purposes is still being conducted by the public. One of the natural substances that are believed to play a role in health is Tamarindus indica. In Indonesia, the material is referred to as "asam jawa". The usefulness of Tamarindus indica in health have been widely trusted by the world community that led to the development of various researches, ranging from in order to know the content and active ingredients of Tamarindus indicaÂ  that may have potential until the mechanism of its role in a variety of conditions in the body. The studies even developed on Tamarindus indicas possible role in the inhibition of cancer. The purpose of this paper is to add our knowledge regarding the use and role of Tamarindus indica in a variety of therapeutic efforts.